Exploring Resources. (Tübingen University Press, 2024)
This book presents case studies of the SFB 1070 ResourceCultures, which use an extended resource definition. Resources are analysed as contingent means to construct, sustain and alter social relations, units and identities. Accordingly, resources are seen as means of social practices of actors that depend on cultural and social appropriation and valuation. They constitute ResourceCultures. The contributions cover the topics of cross-sectional working groups and conferences that shaped the interdisciplinary collaboration on cultural, spatial and temporal dimensions of resources and ResourceCultures.